Chloroquine Triggers Cell Death and Inhibits PARPs in Cell Models of Aggressive Hepatoblastoma - Eloranta, Katja; Cairo, Stefano; Liljeström, Emmi; Soini, Tea; Kyrönlahti, Antti; Judde, Jean-Gabriel; Wilson, David B.; Heikinheimo, Markku; Pihlajoki, Marjut (Frontiers in Oncology, 2020)
Background: Hepatoblastoma (HB) is the most common pediatric liver malignancy. Despite advances in chemotherapeutic regimens and surgical techniques, the survival of patients with advanced HB remains poor, underscoring the need for new therapeutic approaches. Chloroquine (CQ), a drug used to treat malaria and rheumatologic diseases, has been shown to inhibit the growth and survival of various cancer types. We examined the antineoplastic activity of CQ in cell models of aggressive HB. Methods: Seven human HB cell models, all derived from chemoresistant tumors, were cultured as spheroids in the presence of relevant concentrations of CQ. Morphology, viability, and induction of apoptosis were assessed after 48 h and 96 h of CQ treatment. Metabolomic analysis and RT-qPCR based Death Pathway Finder array were used to elucidate the molecular mechanisms underlying the CQ effect in a 2-dimensional cell culture format. Quantitative western blotting was performed to validate findings at the protein level. Results: CQ had a significant dose and time dependent effect on HB cell viability both in spheroids and in 2-dimensional cell cultures. Following CQ treatment HB spheroids exhibited increased caspase 3/7 activity indicating the induction of apoptotic cell death. Metabolomic profiling demonstrated significant decreases in the concentrations of NAD⁺ and aspartate in CQ treated cells. In further investigations, oxidation of NAD+ decreased as consequence of CQ treatment and NAD⁺/NADH balance shifted towards NADH. Aspartate supplementation rescued cells from CQ induced cell death. Additionally, downregulated expression of PARP1 and PARP2 was observed. Conclusions: CQ treatment inhibits cell survival in cell models of aggressive HB, presumably by perturbing NAD⁺ levels, impairing aspartate bioavailability, and inhibiting PARP expression. CQ thus holds potential as a new agent in the management of HB.